Три уровня словообразовательного гнезда - Закарьян, М. (Kalbotyra, 1977)
The prsent paper deals with some questions of the structure of word-building families in the Old Byelorussian language in the period of the 16th–mid-17th centuries. Words as members of such word-building families are treated as units of three different levels: lexical, derivational, grammatical. On each of the levels the word is a unit of two planes: the plane of the content and that of expression. Therefore, the structure of word-building families is investigated on the three levels. And there are the three aspects in which any word-building family should be studied.